DILEMA FILOSOFIS IMPLEMENTASI TEORI HUKUM: STUDI TENTANG PROBLEMATIKA PEMANFAATAN HAK MILIK - Kurniawan, Itok Dwi; AP, Hanuring Ayu (JURNAL LITBANG PROVINSI JAWA TENGAH, 2022)
The purpose of this study is to find out the initial cause of the conflict between the Amungme Papuan indigenous peoples and PT Freeport Indonesia. nd to study legal theory as an academic effort to mediate the resolution of the conflict between the Amungme Papuan indigenous peoples and PT Freeport. Indonesia. The research method is a normative research through library research. The issue of the use of land rights between the Amungme and PT Freeport Indonesia is due to the different basic reasons used by each party to claim the disputed land ownership rights. The Amungme Indigenous tribe adheres to the legal theory of justice which is based on the inheritance of disputed lands which are considered as ancestral lands which automatically belong to the Indigenous Amungme tribe. Meanwhile, from the perspective of PT Freeport Indonesia, they rely on the Contract of Work and Agreement as a solid basis for claiming ownership rights over the disputed land based on the teachings of positivistic legal theory. The philosophical dilemma that occurs between the Amungme Indigenous People and PT Freeport Indonesia, in the author's opinion, can occur because of the basis for using the legal theory used. Through the analysis of the conceptual approach, it is hoped that it can provide answers to disputes by consolidation to find a middle way in the form of joint evidence from each party, then agree on the percentage of land that can be controlled by each party.